Association between egg consumption and metabolic syndrome in Chinese population: a cross-sectional study. Issue 12 (24th December 2021) - Wang, Haochen; Wang, Wanchun; Shen, Minren; Yang, Zidan; Wang, Ning; Zhu, Zhenglei; Wu, Ziying; Xie, Dongxing
Abstract : Objectives: Metabolic syndrome (MS) comprises a constellation of symptoms that include abdominal obesity, hypertension, hyperglycaemia and dyslipidaemia. Dietary intake is a crucial environmental risk factor for MS, but the exact association between MS and egg consumption, which accounts for more than half of the daily total cholesterol intake in Chinese population, has not been previously studied. The aim of this study was to examine the correlation between dietary egg consumption and the prevalence of MS in the context of a large population. Design: A cross-sectional study. Settings: Our study was conducted in a health examination centre in China. Participants: Participants who aged ≥40 years and received routine physical examinations were included for analyses. Main outcome measures: MS was diagnosed in accordance with the clinical diagnosis criteria specified in the American Heart Association Guidelines. Egg consumption was assessed by a validated semi-quantitative food frequency questionnaire. Results: A total of 11 529 participants (46.2% women) were included in the present study. On the basis of multivariable logistic regression analysis, egg consumption was negatively associated with the prevalence of MS after adjusting for dietary energy intake (OR=0.84, 95% CI 0.76 to 0.93, p value for trend=0.001). The above findings did not change with further adjustment for other potential confounders: model 2 was further adjusted for age, body mass index and sex (based on model 1) and model 3 was further adjusted for education level, physical activity level, smoking status, alcohol use status, dietary fat intake, dietary fibre intake and nutritional supplementation (based on model 2). Consistent results were obtained from the analysis in the female subgroup but not in male subjects. Conclusions: A higher level of egg consumption was associated with a lower prevalence of MS in our study participants, and particularly in female subjects.